2018
DOI: 10.2460/javma.253.11.1460
|View full text |Cite
|
Sign up to set email alerts
|

Use of a locking compression plate for equine proximal interphalangeal joint arthrodesis: 29 cases (2008–2014)

Abstract: OBJECTIVE To describe clinical use of a locking compression plate (LCP) for proximal interphalangeal joint (PIPJ) arthrodesis in horses and compare outcomes for horses that underwent the procedure as treatment for fracture of the middle phalanx (P2) versus other causes. DESIGN Retrospective case series. ANIMALS 29 client-owned horses. PROCEDURES Medical records of 2 veterinary teaching hospitals from 2008 through 2014 were reviewed to identify horses that underwent PIPJ arthrodesis of 1 limb. Signalment, surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 17 publications
2
35
1
Order By: Relevance
“…Clinical results from retrospective studies showed that outcomes are better by using LCP (Sakai et al, 2018;Schaer et al, 2010). However, a retrospective study with 82 horses found no significant differences in animal performance among three-screw technique, DCP, and LCP (Herthel et al, 2016).…”
Section: Internal Fixationmentioning
confidence: 96%
See 2 more Smart Citations
“…Clinical results from retrospective studies showed that outcomes are better by using LCP (Sakai et al, 2018;Schaer et al, 2010). However, a retrospective study with 82 horses found no significant differences in animal performance among three-screw technique, DCP, and LCP (Herthel et al, 2016).…”
Section: Internal Fixationmentioning
confidence: 96%
“…Some authors assessed stability improvements using the following implants: two plates (Watt et al, 2002), a T-plate (Steenhaut et al, 1985), a Y-plate (Galuppo et al, 2000), and a spoon plate (Sod et al, 2007). However, clinical results were better using a 3-hole, 4.5-mm DCP (Knox & Watkins, 2006) or LCP (Sakai et al, 2018), when associated with two 5.5-mm transarticular cortex screws. Vidović et al (2020) proposed a new implant, whose fixation system belongs to a new generation of point contact fixators developed in the 1980s (Perren & Buchanan, 1995).…”
Section: Internal Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective study Russell Sakai and colleagues in the USA described the clinical use of a locking compression plate (LCP) for proximal interphalangeal joint (PIPJ) arthrodesis in 29 horses and compared outcomes for horses that underwent the procedure as a treatment for fracture of the middle phalanx (P2) versus other causes .…”
Section: Locking Compression Plate For Pipj Arthrodesismentioning
confidence: 99%
“…Different arthrodesis techniques of the PIPJ have been reported: two diverging 4.5 or 5.5 mm transarticular cortical screws placed in lag fashion (TCS-LF) (Herthel et al, 2016), three parallel 4.5 or 5.5 mm TCS-LF (Read et al, 2005;Carmalt et al, 2010), a combination of dynamic compression plate (DCP) with two 5.5 mm TCS-LF (Sod et al, 2011), a combination of limited-contact dynamic compression plate (LC-DCP) with two 5.5 mm TCS-LF (Rocconi et al, 2015), a combination of locking compression plate (LCP) with two 5.5 mm TCS-LF (Sod et al, 2011;Sakai et al, 2018), double DCP or LCP plating (Cra- , 1995;McCormick and Watkins, 2017) and a combination of a three-hole proximal interphalangeal locking compression plate (PIP plate) with two 5.5 mm TCS-LF (Zoppa et al, 2011;Ahern et al, 2013). The successful outcome of an arthrodesis procedure depends on the method used, the limb affected, the breed of the horse and the underlying pathology present (Schaer et al, 2001;Zubrod and Schneider, 2005;Knox and Watkins, 2006;Sod et al, 2011;Zoppa et al, 2011;Lischer and Auer, 2012;Ahern et al, 2013;Rocconi et al, 2015;Herthel et al, 2016;Sakai et al, 2018). Surgical arthrodesis of the PIPJ using a three-hole PIP plate and two 5.5 mm TCS-LF is currently considered the gold standard (Schaer et al, 2001;Zubrod and Schneider, 2005;Knox and Watkins, 2006;Sod et al, 2011;Zoppa et al, 2011;Lischer and Auer, 2012;Ahern et al, 2013;Rocconi et al, 2015;Herthel et al, 2016).…”
Section: K Baranková Ln Rassmussen Hc Wilderjansmentioning
confidence: 99%